Angiotensin-converting enzyme 2 as a potential therapeutic target for COVID-19: A review - Bhagat Singh; Dheer Singh; Vinod Verma; Ramakant Yadav; Raj Kumar (Elsevier, 2022)
As of August 16, 2021, there have been 207,173,086 confirmed cases and 4,361,996 deaths due to the coronavirus disease (COVID-19), and the pandemic remains a global challenge. To date, no effective and approved drugs are available for the treatment of COVID-19. Angiotensin-converting enzyme 2 (ACE2) plays a crucial role in the invasion into host cells by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the etiological agent of COVID-19. Notably, ACE2 density is influenced by medical conditions, such as hypertension, or by drugs, including angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs), which can change the fate of SARS-CoV-2 infectivity. ACE2 is a target for these drugs and can be manipulated to limit the viral entry and replication within the cells. Different strategies aimed at blocking ACE2 with small molecules, peptides, and antibodies, or by neutralizing the virus through its competitive binding with human recombinant soluble ACE2 (hrsACE2) are currently under investigation. In this article, we review the current state of knowledge that emphasizes the need to find effective therapeutic agents against COVID-19 by exploiting ACE2 as a potential target. The increased soluble ACE2 levels and the application of hrsACE2 in patients with COVID-19 can be implemented to control the disease. It has not yet been established whether hypertension and other comorbidities, independent of age, have a direct role in COVID-19. Therefore, the use of renin-angiotensin system inhibitors, ACEIs and ARBs, should not be discontinued during COVID-19 treatment.